Evaluating the potential of iron-based interventions in methane reduction and climate mitigation - Meidan, Daphne (2024)
Keeping global surface temperatures below international climate targets will require substantial measures to control atmospheric CO2 and CH4 concentrations. Recent studies have focused on interventions to decrease CH4 through enhanced atmospheric oxidation. Here for the first time using a set of models, we evaluate the effect of adding iron aerosols to the atmosphere to enhance molecular chlorine production, and thus enhance the atmospheric oxidation of methane and reduce its concentration. Using different iron emission sensitivity scenarios, we examine the potential role and impact of enhanced iron emissions on direct interactions with solar radiation, and on the chemical and radiative response of methane. Our results show that the impact of iron emissions on CH4 depends sensitively on the location of the iron emissions. In all emission regions there is a threshold in the amount of iron that must be added to remove methane. Below this threshold CH4 increases. Even once that threshold is reached, the iron-aerosol driven chlorine-enhanced impacts on climate are complex. The radiative forcing of both methane and ozone are decreased in the most efficient regions but the direct effect due to the addition of absorbing iron aerosols tends to warm the planet. Adding any anthropogenic aerosol may also cool the planet due to aerosol cloud interactions, although these are very uncertain, and here we focus on the unique properties of adding iron aerosols. If the added emissions have a similar distribution as current shipping emissions, our study shows that the amount of iron aerosols that must be added before methane decreases is 2.5 times the current shipping emissions of iron aerosols, or 6 Tg Fe yr−1 in the most ideal case examined here. Our study suggests that the photoactive fraction of iron aerosols is a key variable controlling the impact of iron additions and poorly understood. More studies of the sensitivity of when, where and how iron aerosols are added should be conducted. Before seriously considering this method, additional impacts on the atmospheric chemistry, climate, environmental impacts and air pollution should be carefully assessed in future studies since they are likely to be important.